Implementation of Microsoft Power Bi in Monitoring Product Sales to Maximize Sales Potential and KPI Sales at PT UPS (PT Unggul Prima Sejati) - Maulidin Amirul Mukminin Hidayat, Gagah (Journal of Social Science and Business Studies, 2023)
This study discusses the implementation of Microsoft Power BI as an effective tool in monitoring product sales and maximizing sales potential. In an increasingly connected and data-driven business era, a deep understanding of sales data and its intelligent use can give companies a competitive advantage. This paper will explain why Microsoft Power BI is the right solution, implementation steps, and its benefits in monitoring product sales and optimizing sales potential.